Hypercalcemia following discontinuation of denosumab therapy: A systematic review - Keisuke Horiuchi (Elsevier, 2021)
Denosumab is a monoclonal antibody that has been approved to treat osteoporosis, skeletal metastasis, and giant cell tumor of bone in skeletally mature patients. Due to its potential adverse effects on normal bone growth, its use has not yet been approved in skeletally immature patients; however, the use of this agent in such patients with overt or dysregulated bone resorptive conditions has been explored in recent years. While most studies have proven the effectiveness of denosumab in controlling the progression of various disorders in skeletally immature patients, they have also revealed that refractory hypercalcemia often follows the discontinuation of denosumab treatment, raising a concern over the use of this agent in these patients. Thus, this study was designed to better understand the pathology of this condition through a systematic review of the published literature. Our analysis suggests that this condition has a potential male predisposition, that there is a correlation between the duration of denosumab treatment and patient age, and that this condition often occurs within 3 months after the last administration of denosumab in skeletally immature patients but is significantly less likely in adults. These results may further underscore that high bone formation and bone turnover rates are critically associated with hypercalcemia after the discontinuation of denosumab. In contrast, given that not all skeletally immature patients develop hypercalcemia, it is probable that other unidentified factors are involved in the pathology of this condition.